Indonesia Hegemoni kekuasaan dalam seri karya Sara Shepard Pretty Little Liars by VIU: Indonesia - Afifah, Lubna Nor (Maliki Interdisciplinary Journal, 2024)
The Indonesian drama "Pretty Little Liars" directed by Emil Heradi was adapted from the American drama of the same title, which was based on the book series by Sara Shepard. whatever they want. Popularity is the level of fame in the eyes of others to be one thing that he is proud of and feared by all those who are under him. And this leads to chaos, bullying and violence. The results of the study, first, the hegemony of power to power carried out by Alissa against three (3) victims and by Person A against one (1) victim with a percentage of 80%. Second, the power over that was carried out by the A to one victim with a percentage of 20%.